2016
DOI: 10.1111/jopr.12551
|View full text |Cite
|
Sign up to set email alerts
|

Status of Removable Dentures and Relationship with Oral Candida‐Associated Factors in a Geriatric Population in Catalonia

Abstract: Elderly people in this study used a complete denture in good condition, with a median age of 15 years. Daily or weekly sugar consumption was found to be highly associated with oral colonization by Candida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…This finding echoes other studies that reported positive correlations between Candida counts and DMFS, DS and FS scores [30,31]. Similar correlations have been reported in some experimental [32] and epidemiological studies [33][34][35][36]. A recent meta-analysis reports that children with oral C. albicans have more than 5 times higher odds of having early childhood caries than those without C. albicans [37].…”
Section: Discussionsupporting
confidence: 87%
“…This finding echoes other studies that reported positive correlations between Candida counts and DMFS, DS and FS scores [30,31]. Similar correlations have been reported in some experimental [32] and epidemiological studies [33][34][35][36]. A recent meta-analysis reports that children with oral C. albicans have more than 5 times higher odds of having early childhood caries than those without C. albicans [37].…”
Section: Discussionsupporting
confidence: 87%
“…This predominance suggests that the hormonal changes following menopause and/or the presence of other age-related diseases may facilitate the development of lesions, particularly among immunocompromised patients. 3,4 Approximately 61% of the participants had some type of chronic disease, and 69.44% were taking medications. These aspects are relevant and should be considered when assessing the efficacy of products, as they might result in unsatisfactory treatment and persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…2 The continuous use of removable dentures has a considerable impact on the development of DS because dentures serve as reservoirs of microorganisms due to irregularities as well as the porousness of the acrylic resin surface and because they hinder the mucosa's self-cleaning. 1,3 DS is usually asymptomatic; however, some patients might experience pain or burning, halitosis, swelling, itching, or xerostomia. 4 DS was classified into three types by Newton solely according to clinical criteria: Type I (pinpoint hyperemia -localized or sparse palatal erythema), Type II (diffuse hyperemia -diffuse erythema, more common), and Type III (granular hyperemia -papillary hyperplasia with rough or nodular mucosa).…”
mentioning
confidence: 99%
“…Removable prostheses promote a favorable microenvironment for the growth of Candida albicans. The oral mucosal-prosthesis interface has low levels of oxygen and pH, 37 which are associated with poor hygiene 38 and reduced salivary flow. These factors likely favor the colonization of C. albicans, and subsequent development of denture stomatitis.…”
Section: Study Of Subgroupmentioning
confidence: 99%